Correction: Optimizing large-scale gambling prevention with adolescents through the development and evaluation of a training course for health professionals: The case of PRIZE. - PLOS ONE Staff (PLoS ONE)
[This corrects the article DOI: 10.1371/journal.pone.0266825.].